The economic expansion in the US since 2009 and Donald Trump's ambitions to "drain the swamp" - Trevor Evans (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
Since the prolonged recession in 1980-82 which laid the basis for the emergence of financeled capitalism in the US there have been four phases of economic expansion. The first three ended with increasingly severe recessions in 1990-91, 2001 and 2007-09. The most recent expansion, which began in mid-2009, has been characterised by relatively low growth and investment has been weaker than in previous expansions. While unemployment has fallen sharply, many of the new jobs have been in low-paid services and the employed rate is below the peak in 2007, with several million workers vanishing from official statistics. While banks have been forced to hold more capital, five giant banks now account for some 50 per cent of the sector's assets. They also run large swathes of the so-called "shadow banking system" that would have collapsed in 2008 without massive state intervention, but which continues to operate as before. The Trump government's much touted investment programme is dependent on mobilising private funding but this has not yet been very forthcoming. And moves to relax the new banking regulations introduced in 2010, while strongly welcomed by the big banks, have been widely criticised. Key indicators of financial tensions are unusually low, but profitability and investment, which usually serve as leading indicators of the business cycle, have begun to decline and this suggests that the current expansion could be approaching an end.
Keywords: F44; G18; E24; J31; 330; US business cycle; banking sector regulation; employment expansion; low wage growth